Faktor Risiko yang Berhubungan dengan Kekuatan dan Ketahanan Genggam pada Remaja - Martini, Ni Putu Laksmi; Mediana, Dian (Jurnal Biomedika dan Kesehatan, 2023)
Background Handgrip strength and endurance are some of the ways that can be done to examine the muscle quality of adolescents as well as their physical fitness. It is influenced by various internal and external factors, including body mass index, gender, age, and smoking habits. Handgrip strength can be an important parameter for health. Adolescents with lower muscle strength have an increased mortality rate in adulthood. Thus, this study aimed to determine the factors associated with handgrip strength and endurance in adolescence. Methods The study used analytic observational with a cross-sectional approach using consecutive non-random sampling on 58 adolescents between 15-23 years old. The instruments used a scale and microtoise to measure body mass index, and a hand dynamometer to measure handgrip strength and endurance. The data was analyzed by the Chi-square test using the SPSS program with p<0.05. Results Of the 58 respondents consisting of 48.27% men, and 51.72% women, there were 58.62% normal BMI and 70.68% did not smoke. The percentage of respondents who had weak grip strength was lower (44.82%) compared to weak grip endurance (55.17%). There was no significant relationship between gender and handgrip endurance; body mass index and handgrip strength as well as handgrip endurance; cigarette consumption and handgrip strength. Moreover, there was found a significant relationship between gender and handgrip strength (p=0.000) and between cigarette consumption and handgrip endurance (p=0.011). Conclusions Handgrip strength and endurance were more in the weak-medium category. There was no significant relationship between gender and handgrip endurance; body mass index and handgrip strength as well as handgrip endurance; cigarette consumption and handgrip strength. Moreover, there was found a significant relationship between gender and handgrip strength and between cigarette consumption and handgrip endurance.